Development economics - Ray, Debraj (Princeton University Press, 1998)
Development Economics will be the definitive textbook in this subject for years to come. It will prove useful to researchers by showing intriguing connections among a wide variety of subjects that are rarely discussed together in the same book. And it will be an important resource for policy-makers, who increasingly find themselves dealing with complex issues of growth, inequality, poverty, and social welfare.